1997
DOI: 10.1046/j.1464-410x.1997.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of primary vesico‐ureteric reflux in male and female infants with pre‐natal hydronephrosis

C.K. YEUNG,
M.L. GODLEY,
H.K. DHILLON
et al.

Abstract: Objective  To examine the characteristics of primary vesico‐ureteric reflux (VUR) in young infants following prenatal hydronephrosis. Patients and methods  The study comprised 155 consecutive infants with VUR detected at a mean age of 8.7 weeks (sd 6.3). Reflux units (n=236) were analysed for relationships between gender, severity of reflux, exposure to urinary tract infection (UTI) and the presence of focal and generalized types of kidney damage on imaging. Bladder wall thickness (from ultrasonography) was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
139
3
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(164 citation statements)
references
References 6 publications
12
139
3
10
Order By: Relevance
“…reports regarding gender distribution of vur patients vary. 10,14,16,21,[30][31][32][33] However, other authors have observed that the male:female ratio in children with reflux is dynamic across different age groups, ranging from a male preponderance in infants to a clear female preponderance in older children. 30,34 it is also important to recognize that the calculated ratio between the sexes is dependent upon the method of ascertainment.…”
Section: Vur Is a Complex Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…reports regarding gender distribution of vur patients vary. 10,14,16,21,[30][31][32][33] However, other authors have observed that the male:female ratio in children with reflux is dynamic across different age groups, ranging from a male preponderance in infants to a clear female preponderance in older children. 30,34 it is also important to recognize that the calculated ratio between the sexes is dependent upon the method of ascertainment.…”
Section: Vur Is a Complex Diseasementioning
confidence: 99%
“…35 However, 80% of cases detected by the appearance of hydronephrosis on prenatal ultrasound are boys, and these patients often have high-grade vur-associated renal damage. 8,33,36 the impact of sex on familial vur was studied by Pirker et al 37 the authors hypothesized that the vur phenotype is caused by more than one genetic disorder and analyzed 159 families with at least 2 children diagnosed with vur. in this study, sisters of female index patients were at a significantly higher risk for vur than brothers (P <0.01).…”
Section: Vur Is a Complex Diseasementioning
confidence: 99%
“…En uno de ellos, efectuado con 108 niños, las lesiones estaban presentes al nacimiento en el 36% de las unidades renales que mostraban reflujo 132 . Los varones sufrirían más este tipo de anomalías renales congénitas 133 . Algunos estudios experimentales indican que estas lesiones de displasia corresponden a una anomalía de la diferenciación del mesonefros en metanefros, sin duda alguna vinculada a una anomalía del desarrollo de la yema ureteral al final del primer mes.…”
unclassified
“…Por el contrario, en un estudio prospectivo se pone de relieve que el 88% de los niños con un RVU diagnosticado por cistografía tiene una orina estéril en el momento del diagnóstico 134 , lo que excluye la infección urinaria como causa de RVU. Además, una gran cantidad de RVU se detecta mediante diagnóstico intrauterino y antes de cualquier episodio infeccioso 133 . En otro estudio prospectivo se afirma que es posible observar auténticas pielonefritis agudas en ausencia de reflujo demostrable: el 63% de los casos de niños presentan una verdadera pielonefritis en la gammagrafía con ácido dimercapto-succínico (DMSA), pero sin reflujo 135 .…”
unclassified
“…VUR is usually a benign condition but can be associated with transient kidney damage, acute inflammation from ascending pyelonephritis, or permanent damage as a consequence of scarring after infection and/or congenital kidney defects histologically comprising renal hypoplasia (too few nephrons) and/or renal dysplasia (incomplete differentiation). [1][2][3] These renal defects are grouped under the term reflux nephropathy (RN). In the United Kingdom, RN accounts for 12% of the approximately 40,000 adults and 7% of the 768 children who require renal transplantation and/or life-long dialysis.…”
mentioning
confidence: 99%